Integrally informed approaches to organizational transformation - Landrum, Nancy E., 1961-; Paul, Jim, 1958- (Journal of organizational change management, 2005)
Integrally informed approaches to organizational leadership and transformation are being increasingly adopted by management educators, consultants, managers, and organizational scholars. In its most concise form, integral approaches simultaneously address the four dimensions of human potential and the developmental levels within each quadrant.